Highly enhanced UV responsive conductivity and blue emission in transparent CuBr films: implication for emitter and dosimeter applications. Issue 39 (28th September 2017) - Vijayaraghavan, Rajani K.; Chandran, Deepak; Vijayaraghavan, Ratheesh K.; McCoy, Anthony P.; Daniels, Stephen; McNally, Patrick J.
Abstract : UV-responsive giant and persistent enhancements in the room temperature electrical conductivity and blue emission in CuBr films in ambient air. Abstract : Highly efficient transparent blue emitters have been pursued for many years, driven in large part by solid-state lighting technology, and the need for blue/UV spectroscopic sources. CuBr is a strong candidate material, chiefly due to its relatively large excitonic binding energies. However, the semiconductor copper halides (CuCl, CuBr, CuI) have been plagued by their relatively inefficient light emission properties, often attributed to intrinsic defect structures. Here we report a novel UV-treatment based approach to achieve massive and persistent enhancements in the room temperature electrical conductivity and blue photoluminescence (PL) in CuBr films in ambient air, an important finding for future light emitting application. After this treatment (typically UV exposure for ∼20 minutes), we have observed an approximately 5 orders of magnitude enhancement in electrical conductivity, and 2 orders of magnitude enhancement in PL, respectively. These enhancements are correlated with the cumulative UV exposure. We also found that the emission energies of the films can be tuned by varying the excitation wavelength. A mechanism based on the formation of luminescent excimer/exciplexes with cuprophilic interactions is proposed to explain the observed unusual photophysical characteristics. The potential of these films for UV dosimeter application is demonstrated by fabricating a device and monitoring the current readout as a function of UV dose, which is substantially sensitive to a dose range of 1–1000 mJ cm −2 . This work provides valuable insights into the interesting photophysical properties of CuBr films, and opens a pathway to their deployment across a wide range of applications.